GENDER DECONSTRUCTION IN AL KHALLAT+ - Muhammad Irfan Maulana; Falih Hilmi Adi (Journal of Arabic Literature (JaLi), 2023)
Alkhallat+ is one of the films from Saudi Arabia published on Netflix featuring four themes about deceit. The interesting part of this film is the existence of misogynistic values by the author that can bring out the opposite meaning of favoring women. This research will analyze the gender issue in the film using Jacques Derrida's Deconstruction theory, which brings the concept of binary opposition to gender. This theory is used to explore the idea of deconstruction reflecting misogynistic values in the movie. The result reveals that "the other" means women are not weak and susceptible creatures. Women can feel with their hearts if something terrible happens. Men also need women. This idea also rejects the stigma that all men can live alone without the help of women, whom men consider weak and less powerful.